Pengaruh Desain Produk, Promosi, Dan Harga Terhadap Keputusan Pembelian Purbasari Lipstick Color Matte Di Toko Sehat Cosmetic Kota Mojokerto - Resty Dwi Priyantari (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Currently, many women who like to try new cosmetics including cosmetics type lipstick. Based on many types, colors, designs and brands of lipstick offered in various cosmetic outlets became one of the considerations for people to choose the right lipstick as needed. This study aims to (1) find out how big the influence of product design on purchasing decision of Purbasari lipstick color matte at Toko Sehat Cosmetic Mojokerto (2) to know how big influence of promotion to purchasing decision of Purbasari lipstick color matte at Toko Sehat Cosmetic Mojokerto (3) Big influence of price to purchasing decision of purbasari lipstick color matte at Toko Sehat Cosmetic Mojokerto. Based on the results of data analysis that has been done indicate that product design, promotion, and price have a positive and significant effect on buying decision of Purbasari lipstick color matte at Toko Sehat Cosmetic Mojokerto . The variable that gives more dominant influence is promotion variable that is equal to 0,345. Keywords: Product Design, Promotion, Price, Purchase Decision